LIFE VALUES OF MANGGARAI PEOPLE AS REFLECTED IN THE ORAL TRADITION GO’ET - Salahuddin Salahuddin (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2023)
This study aims to examine the philosophical life values of the Manggarai people in Western Flores, which are reflected in the proverbs of the Manggarai language (Go'et). Go'et is an oral literature that contains the values that govern the life of the Manggarai people. This study uses a qualitative descriptive approach design involving semantics theory to interpret the meaning of Go'et. The data in this study were obtained by conducting in-depth interviews with one of the Manggarai community leaders with the initials AW (52) and secondary data available on the Manggarai Nuca Lale website. The data obtained were then validated using the Indonesian-Mangarai dictionary to find samples that fit this study. Nine data are relevant to the scope of this study based on the results of data collection that have been done. From the data found, the researcher concluded that there are three central values in go'et which contain advice and instructions for living a life under the norms that apply to the Manggarai community, such as unity, Manners and Wisdom, and passion and hard work. These findings are consistent with the fact that the Manggarai people uphold the values of unity, cooperation, and harmony among community members.